Estratégias de difusão implementadas no Museu de Arte Sacra de Santa Maria/RS - Belizio, Luciana de Aguilar (2016)
The Sacred Art Museum of Santa Maria, a private institution belonging to the Metropolitan Cathedral of Santa Maria, develops conservation actions and management of cultural goods that identify Catholicism in Santamariense society. This work, adhered to overcome the difficulties that the institution had in the dissemination and marketing sector and propose actions with a view to encouraging greater access to its collection, by building a virtual site (website) containing institutional information of Museum. Therefore, an interactive model of the Museum premises was created for virtual visit, which was made available to the public a photographic exhibition of the Museum's collection. To overcome the difficulties of the museum, it has been implemented yet another strategy, promotion and updating Museological Plan of museum. The results showed that the actions taken were able to promote significantly the Museum, through the website (final product), and a consolidated presence on social networks, verified by the number of shares and likes in their online presence channels. Besides that, the promotion strategies conducted reached a broad range over the estimated statistics for this search.